Analysis of the Effect of International Trade on State Expenditure - M. Fauzan Rusyidi Nst; Rizky Rizky; Suhendi Suhendi; Andria Zulfa; Lia Nazliana Nasution (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
This research aims to figure out how international trade influence the government expenditure. The independent variables of this research are export and import. The dependent variable of this research is government expenditure. The method of this research is OLS. This research use datas from World Bank and BPS. The object of this research is the economic condition of Indonesia. The result of this research are as follows : Export significantly influence the government expenditures. Import doesn’t significantly influence government expenditures. Export and import simultantly influence the government expenditures.